2019
DOI: 10.1080/03019233.2019.1680176
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the formability of ultrahigh-strength sheet material using local heat treatment

Abstract: In this study, the effects of local heat treatment temperature on the V-bending formability of Martensitic 1200 steel, was investigated experimentally. In the first stage of the study, local heating temperatures were determined according to the stress-strain curves obtained as a result of the hot tensile test. Other experimental parameters included temperature (room temperature -RT/25, 300, 400 and 500°C), die-punch angle (30, 60, 90 and 120°) and punch holding time (0 and 10 s). The heating procedure in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…It is known that the martensite ratios and hardness of DP steel materials, which contain martensite and ferrite phases in their microstructure, are reduced when they are heated compared to their room temperature conditions, in general [13,14]. Similar to this known situation, it was observed that the martensite ratios and hardness values of the DP800 samples decreased with the increase of the laser power used compared to the RT conditions.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It is known that the martensite ratios and hardness of DP steel materials, which contain martensite and ferrite phases in their microstructure, are reduced when they are heated compared to their room temperature conditions, in general [13,14]. Similar to this known situation, it was observed that the martensite ratios and hardness values of the DP800 samples decreased with the increase of the laser power used compared to the RT conditions.…”
Section: Resultsmentioning
confidence: 83%
“…It has been observed that the rate of ferrite in the material increases with the increase in temperature in locally applied heat treatments when various studies in the literature are examined. In this way, it has been observed that the amount of springback could be reduced and the formability feature could be increased [6][7][8][9][10][11][12][13][14][15][16][17][18]. During the forming of high-strength sheet metal materials at room temperature, dimensional forming errors which are called springback may also occur in addition to difficulties such as crack formation and breakage.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers [16][17][18] have stated that the springback of sheet material is associated with tangential stresses. Looking again at the studies [19][20][21][22], an increase in holding time is shown to reduce the elastic return of the material, thus reducing the springback. In the present study, it was useful to consider the effect of holding time together with punch radius and die angle.…”
Section: Resultsmentioning
confidence: 99%
“…2). Only local heating was applied [18]. The warm forming process is often used to reduce springback in metal forming [19,20].…”
Section: Methodsmentioning
confidence: 99%